Developing and Reflecting on a Black Disability Studies Pedagogy: Work from the National Black Disability Coalition - Dunhamn, Jane; Harris, Jerome; Jarrett, Shancia; Moore, Leroy; Nishida, Akemi; Price, Margaret; Robinson, Britney; Schalk, Sami (Disability Studies Quarterly, 2015)
This collection of writing has grown from the work of the National Black Disability Coalition, led by Jane Dunhamn and Leroy Moore. The Coalition met on June 7, 2013, in the historic Shiloh Baptist Church in Trenton, New Jersey to discuss the future of Black Disability Studies (BDS). Since that time, members of the Coalition have written an outline for a BDS course, presented at conferences, and developed strategies to incorporate BDS into the disciplines of Black Studies and Disability Studies. We have also reflected deeply on what the introduction of BDS will mean, both for Black Studies and for disability studies. Our writings in this collection are intended to mark the work of the National Black Disability Coalition thus far, but also to provide a platform from which further work in BDS can grow. By underscoring the development and potential of BDS, this article articulates the need for BDS within mainstream disability studies, and advocates for BDS not to be taken as a marginalized special-topic course, but rather to be engaged in every and at the heart of Disability Studies courses and pedagogies. Although we believe that BDS should be integrated into every Disability Studies course, we recognize that, like disability itself, it cannot simply be “added and stirred”; rather, the inclusion of BDS is a paradigm-shifting change. The pieces included in this collection are enactments of an ongoing conversation–a conversation that we hope the readers of Disability Studies Quarterly will join thoughtfully. The sections comprise statements from the leaders of the National Black Disability Coalition, Jane Dunhamn and Leroy Moore; reflective writings from three instructors and two students of Black Disability Studies; and a copy of the course outline.